MODAL SOSIAL DALAM PEMASARAN PRODUK HERBAL PENAWAR ALWAHIDA INDONESIA (HPAI) DI BUSINESS CENTER (BC) 4 KOTA PEKANBARU - Ima Kusmira; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Business Center (BC) Herbal Bidder Alwahida (HPAI) Pekanbaru is an HPAI business service center that can serve all HPAI stockists, both stockists under the leader network (Business Center owner) and stockists outside the leader network. Business in Herbal Bidders Alwahida Indonesia has the term commercial status / rank from the highest to the lowest, namely Business center (BC), Agency Center (AC), Distributor Center (DC), and Stock Center (SC). This research was conducted in the city of Pekanbaru. The purpose of this study is to determine what elements of social capital are in HPAI Business Center (BC) 4, and to find out how strong the social capital is. This research uses descriptive quantitative method, in determining the research sample using proportional sampling technique, namely the use of balanced representation, while the number of respondents in this study amounted to 79 people.  he population in this study is the agent level, namely Agency Center (AC), Distributor Center (DC), Stockist. Data collection was carried out by observation, interviews after preparing a list of questions or questionnaires, and documentation. The theory used is the Social Capital Theory. The results of the research in the field can be concluded that there are 3 elements of social capital in Herbal Bidders Alwahida Indonesia, namely networks, trust, and social norms. Among the 3 elements, each level of social capital is strong, medium, and weak. Among the 3 elements of social capital that have the greatest number are the elements of network social capital. And social capital is very influential on the points earned by each agent. If social capital is strong, the points will be large.  Keywords: Social Capital, Business Center (BC) and Strategy